A Class II KNOX Gene, KNAT7-1, Regulates Physical Seed Dormancy in Mungbean [Vigna radiata (L.) Wilczek] - Laosatit, Kularb; Amkul, Kitiya; Yimram, Tarika; Chen, Jingbin; Lin, Yun; Yuan, Xingxing; Wang, Lixia; Chen, Xin; Somta, Prakit (Frontiers in Plant Science, 2022)
Seed dormancy in wild mungbean (Vigna radiata var. sublobata) may be useful for the breeding of cultivated mungbean (var. radiata) with pre-harvest sprouting resistance. Previous studies have identified two major quantitative trait loci (QTLs) for seed dormancy, HsA and Sdwa5.1.1+, in wild mungbean that are possibly having the same locus or linked. However, these QTLs have not been confirmed/verified and a molecular basis of seed dormancy in mungbean is not yet known. In this study, we aimed to finely map the Sdwa5.1.1+ and identify candidate gene(s) for this locus. Microscopic observations revealed that wild mungbean “ACC41” seeds had a palisade cuticle layer, while cultivated mungbean “Kamphaeng Saen 2” (KPS2) seeds lacked this layer. Fine mapping using an F2 population developed from a cross between ACC41 and KPS2 revealed two linked QTLs, Sdwa5.1.1+ and Sdwa5.1.2+, controlling seed dormancy. The Sdwa5.1.1+ was confirmed in an F2:3 population derived from the same cross and mapped to a 3.298-Kb region containing only one gene LOC106767068, designated as VrKNAT7-1, which encodes the transcription factor KNOTTED ARABIDOPSIS THALIANA7 (KNAT7), a class II KNOTTED1-LIKE HOMEOBOX (KNOX II) protein. VrKNAX7 sequence alignment between ACC41 and KPS2 revealed several polymorphisms in the coding, untranslated, and promoter regions. Quantitative real-time PCR (qRT-PCR) analysis revealed that the expression of VrKNAT7-1 and VrCYP86A, a putative downstream regulation of VrKNAT7-1, in the seed coat of ACC41 is statistically much higher than that of KPS2. Altogether, these results indicate that VrKNAT7-1 controls physical seed dormancy in the wild mungbean ACC41.